Doppler ultrasound findings in healthy wrists and finger joints. Issue 6 (12th May 2004) - Terslev, L; Torp-Pedersen, S; Qvistgaard, E; von der Recke, P; Bliddal, H
Abstract : Objective: To evaluate the presence of flow by Doppler ultrasound (DUS) in the wrist and finger joints (carpometacarpal 1 (CMC1), metacarpophalangeal (MCP), and proximal interphalangeal (PIP) joints) of healthy controls. Methods: Twenty seven healthy volunteers (15 women, 12 men; mean age 45 years, range 18–93) with a total of 324 joints were examined by DUS. The synovial vascularisation was determined by colour Doppler and the spectral Doppler resistive index (RI). Patients were only included if no synovitis was suspected at the clinical examination and the values for biochemical analysis were within the normal range. Results: We found colour pixels in 15 of the 27 examined wrist scans and in 8 of these a measurable RI. In the CMC1 joint, colour pixels were found in 11 of the 27 scans and in 9 of these a measurable RI. For the MCP joints, colour pixels were found in 10 out of 135 scans and in 3 of these a measurable RI. The mean RI for all three types of joints was 0.85 and the mean pixel fraction varied from 0.05 to 0.08. Only one PIP joint scan was found to have colour pixels and a flow with an RI of 0.67. Conclusion: Synovial vascularisation may be detected in healthy subjects using DUS. Newer US machines have higher Doppler sensitivity, and it is necessary to be able to distinguish normal from pathological synovial flow.